PELATIHAN PEMBUATAN ALAT PERMAINAN EDUKATIF POHON HIJAIYAH DI TK AL FIKRI KOPANG LOMBOK TENGAH (NTB) - Muhibbin, Muhibbin; Harjanty, Rokyal; Mariataun, Mariataun; Rohani, Rohani (Insanta : Jurnal Pengabdian Kepada Masyarakat, 2024)
Educational game tool is one of the Creative Learning media that can be developed by teachers in supporting the learning process so that the learning process is done to be fun and can attract the attention of early childhood. The purpose of this community service activity is to provide training in Making Educational Game Tools Hijaiyah tree in kindergarten Al Fikri Kopang Central Lombok. The method used in this service is the service learning method which consists of two stages, namely material exposure and demonstration. As for the participants, there were 2 teachers in TK Al Fikri Kopang Central Lombok.. The results of the implementation of this service activity teachers can create hijaiyah letter trees that can help support the learning process from simple materials, besides that teachers can create and be able to implement educational Hijaiyah trees in early childhood learning.